\documentclass{article} \usepackage{amsmath} \usepackage{amssymb} \begin{document} \title{Mathematics Assignment 2 --- Matrices} \author{Ahmad Saalim Lone, 2019BCSE017} \date{05 May, 2020} \maketitle \section*{Question 1} If \( A = \begin{bmatrix} 3 & 3 & 4 \\ 2 & -3 & 4 \\ 0 & -1 & 1 \end{bmatrix} \) find $A^{-1}$ and verify that $A^{-1}A = I = AA^{-1}$. \subsection*{Solution} \begin{align*} A &= \begin{bmatrix} 3 & 3 & 4 \\ 2 & -3 & 4 \\ 0 & -1 & 1 \end{bmatrix} \\ A^{-1} &= \frac{adj(A)}{|A|} \\ |A| &= 3 \times (-3 + 4 ) - 3 \times 2 + 4 \times -2 \\ |A| &= -11 \\ \text{Cofactor matrix of A } &= \begin{bmatrix} 1 & 2 & -2 \\ 7 & 3 & -3 \\ 24 & 4 & -15 \end{bmatrix} \\ adj(A) &= \begin{bmatrix} 1 & 7 & 24 \\ 2 & 3 & 4 \\ -2 & -3 & -15 \end{bmatrix} \\ A^{-1} &= \begin{bmatrix} \frac{1}{11} & \frac{2}{11} & -\frac{2}{11} \\[6pt] \frac{7}{11} & \frac{3}{11} & -\frac{3}{11} \\[6pt] \frac{24}{11} & \frac{4}{11} & -\frac{15}{11} \end{bmatrix} \end{align*} \begin{align*} A \times A^{-1} &= \begin{bmatrix} \frac{1}{11} & \frac{2}{11} & -\frac{2}{11} \\[6pt] \frac{7}{11} & \frac{3}{11} & -\frac{3}{11} \\[6pt] \frac{24}{11} & \frac{4}{11} & -\frac{15}{11} \end{bmatrix} \begin{bmatrix} 3 & 3 & 4 \\ 2 & -3 & 4 \\ 0 & -1 & 1 \end{bmatrix} \\ &= \begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1 \end{bmatrix} \\ &= I \end{align*} Similarly, $A^{-1}\times A = I$ \section*{Question 2} Find the inverse of \( A =\begin{bmatrix} 1 & 2 & 1 \\ 3 & 2 & 3 \\ 1 & 1 & 2 \end{bmatrix} \) by applying E-transformation. \subsection*{Solution} \[ \begin{bmatrix} 1 & 2 & 1 \\ 3 & 2 & 3 \\ 1 & 1 & 2 \end{bmatrix} = \begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1 \end{bmatrix} A \] After applying the following transformations \begin{align*} C_3 &\to C_3 - C_1 \\ C_2 &\to \frac{C_1}{2} \\ R_1 &\to R_1 - R_2 \\ R_1 &\to \frac{R_1}{-2} \\ C_1 &\to C_1 - C_3 \\ R_2 &\to R_2 - 3R1 \\ R_2 &\to R_3 - \frac{R_2}{2} \end{align*} we get \begin{align*} \begin{bmatrix} 1 & 0 & 0 \\ 0 & 1 & 0 \\ 0 & 0 & 1 \end{bmatrix} &= \begin{bmatrix} -1 & \frac{1}{4} & \frac{1}{2} \\[6pt] 3 & -\frac{1}{4} & -\frac{1}{2} \\[6pt] -\frac{5}{2} & \frac{1}{8} & \frac{3}{4} \end{bmatrix} \times A \\ \therefore A^{-1} &= \begin{bmatrix} -1 & \frac{1}{4} & \frac{1}{2} \\[6pt] 3 & -\frac{1}{4} & -\frac{1}{2} \\[6pt] -\frac{5}{2} & \frac{1}{8} & \frac{3}{4} \end{bmatrix} \end{align*} \section*{Question 3} Reduce the matrix \( A = \begin{bmatrix} 1 & -1 & 2 & -3 \\ 4 & 1 & 0 & 2 \\ 0 & 3 & 0 & 4 \\ 0 & 1 & 0 & 2 \end{bmatrix} \) to the normal form and hence determine its rank. \subsection*{Solution} To reduce the matrix we apply the following operations \begin{align*} R_1 &\to R_1 + R_3 \\ R_4 &\to R_4 - R_2 \\ R_2 &\to R_2 + R_4 \\ C_2 &\to C_2 - C_3 \\ C_4 &\to C_4 - C_2 \\ R_3 &\to R_3 - R_2 \\ C_2 &\rightleftharpoons C_3 \\ C_2 &\to \frac{C_2}{2} \\ R_3 &\to \frac{R_3}{2} \\ R_4 &\to \frac{R_4}{2} \\ C_4 &\to C_4 - C_2 \\ C_3 &\to C_3 - C_4 \\ C_4 &\rightleftharpoons C_2 \\ R_4 &\to R_4 - R_1 \\ R_4 &\to -R_4 \\ R_1 &\to R_1 - R_4 \end{align*} At the end we arrive at \[ \begin{bmatrix} 1 & 0 & 0 & 0 \\ 0 & 1 & 0 & 0 \\ 0 & 0 & 1 & 0 \\ 0 & 0 & 0 & 1 \end{bmatrix} \] i.e. $[I_4]$ $rank = 4$ \section*{Question 4} Reduce the matrix \(A = \begin{bmatrix} -2 & -1 & -3 & -1 \\ 1 & 2 & 3 & -1 \\ 1 & 0 & 1 & 1 \\ 0 & 1 & 1 & -1 \end{bmatrix} \) to Echelon form and find its rank. \subsection*{Solution} To convert it into Echelon form, we apply the following transformations. \begin{align*} R_1 &\to R_1 + R_2 \\ R_1 &\leftrightharpoons R_4 \\ R_2 &\to R_2 - R_3 \\ R_2 &\to \frac{R_2}{2} \\ R_3 &\to R_3 + R_4 \\ R_2 &\to R_2 - R_1 \\ R_3 &\to R_3 - R_1 \\ R_3 &\leftrightharpoons R_4 \\ R_2 &\leftrightharpoons R_3 \\ R_1 &\leftrightharpoons R_2 \\ R_1 &\to -R_1 \end{align*} We get \[ \begin{bmatrix} 1 & -1 & 0 & 2 \\ 0 & 1 & 1 & -1 \\ 0 & 0 & 0 & 0 \\ 0 & 0 & 0 & 0 \end{bmatrix} \] \[ rank = 2 \] \section*{Question 5} Solve \begin{align*} x + y + z &= 9 \\ 2x + 5y + 7z &= 52 \\ 2x + y - z &= 0 \end{align*} \subsection*{Solution} \begin{align*} \Delta &= \begin{vmatrix} 1 & 1 & 1 \\ 2 & 5 & 7 \\ 2 & 1 & -1 \end{vmatrix} = -4 \\ \Delta_1 &= \begin{vmatrix} 9 & 1 & 1 \\ 52 & 5 & 7 \\ 0 & 1 & -1 \end{vmatrix} = -4 \\ \Delta_2 &= \begin{vmatrix} 1 & 9 & 1 \\ 2 & 52 & 7 \\ 2 & 0 & -1 \end{vmatrix} = -12 \\ \Delta_3 &= \begin{vmatrix} 1 & 1 & 9 \\ 2 & 5 & 52 \\ 2 & 1 & 0 \end{vmatrix} = -20 \\ x &= \frac{\Delta_1}{\Delta} = 1 \\ y &= \frac{\Delta_2}{\Delta} = 3 \\ z &= \frac{\Delta_3}{\Delta} = 5 \end{align*} \section*{Question 6} Test the consistency of: \begin{align*} 3x - y + 2z &= 3 \\ 2x + y + 3z &= 5 \\ x - 2y - z &= 1 \end{align*} \subsection*{Solution} \[ \text{Augemented matrix} = \begin{bmatrix} 3 & -1 & 2 & : & 3 \\ 2 & 1 & 3 & : & 5 \\ 1 & -2 & -1 & : & 1 \end{bmatrix} \] \[ \Delta = \begin{vmatrix} 3 & -1 & 2 \\ 2 & 1 & 3 \\ 1 & -2 & -1 \end{vmatrix} = 10 \] \[ \Delta \ne 0 \therefore \text{it is consistent with the unique solution} \] \section*{Question 7} Solve the equations \begin{align*} x + 3y - 2z &= 0 \\ 2x -y + 4z &= 0 \\ x - 11y + 14z &= 0 \end{align*} \subsection*{Solution} \begin{align*} \Delta =\begin{vmatrix} 1 & 3 & -2 \\ 2 & -1 & 4 \\ 1 & -11 & 14 \end{vmatrix} &= 0 \\ \Delta_1 = \Delta_2 = \Delta_3 &= 0 \\ \therefore \text{unique solution is } x = y = z &= 0 \end{align*} \end{document}